Notary Role In Assets Transfer Process From a Hospital Foundation Become a Limited Company - Siti Anggraini; Lathifah Hanim; Djunaedi Djunaedi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The establishment of foundations in Indonesia prior to the foundation law was only based on customary law/jurisprudence in practice that developed in the community. The establishment of the foundation itself sometimes deviates from its original purpose, namely as a non-profit copper company with social, religious, and humanitarian purposes, but in the future it is not uncommon for the founders and coaches of a foundation to want to make a profit/profit from their business. The author deliberately takes a case study of a hospital foundation that changes a legal entity and its assets into a PT, namely the author wishes to be able to find out the extent of the role and responsibilities of a notary, and what about this matter when viewed from the point of view of the foundation's laws and regulations. - law PT, whether it is an unlawful act or not. The author in carrying out this case study research, uses a normative juridical method, namely by examining theories and concepts, as well as legal principles and legislation related to research. The results of the study can be concluded by the author that changing a legal entity from a foundation to a PT, is a violation of the law, because it is contrary to the laws and regulations of the foundation and the laws and regulations of PT.